PENGARUH IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN SALES GROWTH TERHADAP NILAI PERUSAHAAN - Ni Kadek Arta Fani; Ni Wayan Yuniasih (Hita Akuntansi dan Keuangan, 2021)
Firm value is the value possessed by a company which becomes an illustration for investors regarding the company's success rate in managing its resources. This study aims to analyze the effect of implementing corporate social responsibility and sales growth on firm value. CSR disclosure is measured by the CSRDI proxy, sales growth is proxied by comparing sales in year t after deducting the sales of the previous period against sales in the previous period, and company value is measured by the PBV proxy. The research was conducted in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2017 to 2019. A sample of 21 companies were selected by purposive sampling. The data analysis technique used is multiple linear regression analysis. The results showed 1) corporate social responsibility has a significant positive effect on firm value. 2) sales growth has a significant positive effect on firm value.